The Influence of Nurse Knowledge Level on Compliance Implementation of Early Warning Score and Code Blue System in the Inpatient Room - Syahrul Hidayat; Yuly Peristiowati (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Early Warning Score (EWS) is an early detection system to predict the deterioration of the patient's condition. The Code Blue System is an emergency procedure code that must be activated immediately if someone is found in a condition of respiratory or cardiac arrest in the hospital area. The purpose of this study was to determine the effect of the level of knowledge of nurses on adherence to the implementation of the early warning score and the Code Blue System. The research method used is Systematic Literature Review which is based on online data on Google Scholar, and Pubmed. Articles were searched from January – March 2023. 6 articles from each database, the majority stated that there was an influence on the level of knowledge of nurses on adherence to the implementation of the early warning score and the code blue system.